The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5812/ircmj.88324
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Brain-Derived Neurotrophic Factor and Creatinine During Ramadan Fasting: A Prospective, Controlled Clinical Trial

Abstract: Background: Brain-derived neurotrophic factor (BDNF) is associated with mood-related symptoms. Fasting can improve mood. However, there was a lack of information about BDNF during prolonged fasting in Summertime in Germany. Objectives: This study aimed to determine (1) the effect of Ramadan fasting on BDNF and creatinine during the month of Ramadan in Germany; (2) the correlation of BDNF with body composition parameters and Health-related Quality of Life (HQoL). Methods: This prospective controlled clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In patients, RF should be carefully monitored by health professionals. Other studies also reported the effect of RF on young males [16][17][18], workers [19], tennis players [20] and taekwondo athletes [21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In patients, RF should be carefully monitored by health professionals. Other studies also reported the effect of RF on young males [16][17][18], workers [19], tennis players [20] and taekwondo athletes [21].…”
Section: Introductionmentioning
confidence: 96%
“…A long period of fasting could influence different aspects of the human body, including at genetic level [22,23] and its phenotypic manifestations; for example, one study showed the changing in health-related quality of life and body composition (BC) parameters [16]. Another study showed the alteration of creatinine levels during a long fasting period in young males, although it is still in health range [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nine of the sixteen studies were experimental, while the other seven studies were observational. Five of the sixteen studies were executed during the month of Ramadan [25,26,[28][29][30]. Three of the five RIF studies revealed reductions in BDNF levels [25,26,30], while the rest (two studies) revealed an increase in BDNF levels during/after the observance of RIF [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus brain cells can counteract the nutritional and metabolic stressors associated with fasting 18 . Interestingly, the serum level of BDNF was significantly increased in Ramadan's last days compared with the first days 19 …”
Section: Discussionmentioning
confidence: 98%
“…18 Interestingly, the serum level of BDNF was significantly increased in Ramadan's last days compared with the first days. 19 All these factors may collectively explain why the frequency and intensity of migraine attacks decreased significantly in Ramadan's last 10 days compared with the first 10 days. Accordingly, physicians should reassure the patients with migraine that Ramadan's exacerbating effect on their migraine attacks is only limited to the first 10 days of fasting and then subsides with the successive days of fasting.…”
Section: Discussionmentioning
confidence: 99%